Fine needle aspiration and core needle biopsy of the spleen: A case series illustrating current practices and challenges. Issue 11 (21st September 2021) - Neal, Daniel; Robila, Valentina; Chesney, Alden; Sayeed, Sadia
Abstract: Introduction: Splenic fine needle aspiration (FNA) and core needle biopsies (CNB) are rare specimen types, potentially avoided due to clinical concern for hemorrhagic complications. The safety and utility of splenic FNA, the role of rapid onsite evaluation (ROSE), as well as the diagnostic utility of CNB versus FNA have not been recently reviewed. Materials and methods: A 10‐year retrospective review was performed of percutaneous image‐guided FNA and CNB of the spleen. Clinical indications, outcomes, ROSE findings, and final diagnoses were reviewed and correlated. Results: Forty‐four specimens from 39 patients were identified. The commonest indication for biopsy was a radiographic mass found during assessment for patient complaint (45%, 20/44), evaluation for malignancy (primary or metastatic) (39%, 17/44), and incidentally (16%, 7/44). Malignant diagnoses were rendered in 10 cases, 80% hematolymphoid and 20% nonhematolymphoid. Thirty‐one cases were nonneoplastic and identified as infectious/inflammatory processes 39%, cysts 10%, vascular lesions 13%, benign splenic elements 22%, accessory or atrophic spleen 10%, and extramedullary hematopoiesis 6%. The nondiagnostic rate was 7%. Cases with subsequent splenectomy showed 100% specificity and 86% sensitivity. The concordance of ROSE and final interpretation was 90% within the neoplastic category. Finally, the significant complication rate was 6.8% with no bias to occurrence following FNA or CNB. Conclusions: This series affirms the safety and efficacy of splenic FNA and CNB by complication rates comparable to prior studies and high rate of concordance. The diagnostic accuracy may be further improved by ROSE, and CNB in cases reliant on staining and tissue architecture.